Necrotising soft tissue infection in the present era: an analysis of clinicopathological features and predictors of mortality - Dr Alok Anshu; Dr Surjeet Dwivedi; Dr M Murali; Dr Harsha MP (Surgery in Practice and Science, 2023)
Background: Necrotizing soft tissue infections (NSTI) and non-NSTI are frequently difficult to distinguish based on symptoms, signs, and investigations. High morbidity related to it can only be avoided by early detection and treatment. Aim: This study examined demographic, clinicopathological, NSTI prognosis, and mortality factors. Methodology: 80 NSTI patients were retrospectively studied. Clinicopathological profile, surgical management, histological report, and LRINEC score were included. Mortality predictions were evaluated between survivors and non-survivors. Results: 73.8 percent of patients were male and the mean age was 55.4±9.6 years. Nonsurvivors averaged 11.88±0.72 LRINEC scores. Non-survivor CRP averaged 236.5±48.5 mg/l. Gp A Hemolytic Streptococci were most frequent (37.8 percent ). Diabetes was a significant mortality predictor. Total mortality was 20%. Conclusion: NSTI remains a major killer. High mortality is linked to age, diabetes, higher blood creatinine, MODS, and delayed surgery.” and proceed accordingly.